Prarancangan Pabrik Fatty Alcohol (Alkohol Lemak) Dari CPO (Crude Palm Oil) Dengan Disain Alat Utama Reaktor Hidrogenasi Jenis Fixed Bed Multitube - Supriyanti Supriyanti; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Fatty alcohol is a derivative of vegetable fats and animal oils, and is a non-oil and gas export commodity that is needed by various industries such as perfumes, cosmetics, pharmaceuticals, food and beverages. demand for alcohol is increasing every year. The import of alcohol has been carried out, but the domestic demand for alcohol has not been met. This has led to the establishment of a fatty alcohol factory with crude palm oil as the main raw material to meet these needs. The plant has an annual production capacity of 130,000 tons and will be established in Pelintung, Dumai. The production of fatty alcohols is carried out through three processes: pretreatment, transesterification and hydrogenation. The main equipment of this tool is designed as a hydrogenation reactor, which functions to react methyl ester with hydrogen with the help of a CuCr catalyst. The operating temperature used is 1700C with an operating pressure of 100 bar. The hydrogenation reactor is 4,006 m (157.72 in) high and uses skirt supports. Factory economic analysis is carried out to determine the feasibility of the factory to be built. Based on the results of the economic feasibility analysis of the factory, the Fatty alcohol factory is feasible to be built with IRR 24.164%, ROI 27.35% and BEP 58%.Keywords: Crude palm oil, economic analysis, fatty alcohol, hydrogenation, transesterification